Severe mental illness & employment: cost-benefit analysis and dynamics of decision making. Issue 4 (4th November 2014) - Booth, David; Francis, Simon; Mcivor, Neil; Hinson, Patrick; Barton, Benjamin
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore the economic benefits of Individual Placement with Support programmes commissioned by NHS North in the North West and Yorkshire and Humber regions. Design/methodology/approach – A literature review was conducted and data collected from supported employment programmes in four localities. An econometric analysis was performed to evaluate likely savings for local commissioners and return on investment for the Treasury. Findings – Integration of employment support within mental health services is central to success. Econometric analysis showed that local commissioners could save £1, 400 per additional job outcome by commissioning evidence-based interventions and there is a positive return on investment to the Treasury for every £1 spent there is a return to the Treasury of £1.04. Originality/value – This paper demonstrates the economic and social value of evidence-based supported employment for people with severe mental illness. The economic data generated could be helpful in encouraging investment in effective employment support in other areas. The work, views and perspectives contained in this paper are those of the authors. It does not necessarily reflect the views of the organisations for whom the authors work.